Pergerakan Non-Playable Character dalam Game Stealth Menggunakan Finite State Machine - Angga Adetiya; Hanny Haryanto; Erlin Dolphina; Erna Zuni Astuti; Muljono Muljono (EXPERT: Jurnal Manajemen Sistem Informasi dan Teknologi, 2023)
Movement of Non-Playable Character in Stealth Game using Finite State Machine - Stealth is a game genre that relies on hiding skills and strategizing to complete missions. Challenges in the form of enemy Non-Playable Character (NPC) are one of the vital elements of this genre game. However, NPCs generally only move according to a predetermined line or path of movement, so that their movements can be estimated easily after the player has seen them several times. This causes the movement of NPCs to look monotonous and not challenging. Finite State Machine (FSM) is an artificial intelligence method that can simply model enemy behavior. FSM consists of states and transitions where the state is the current state of the NPC, while the transition is the state of a state. This study models the behavior of enemy NPCs in stealth games using FSM so that it is not easy to predict their movements by adjusting idle time, walking, and moving speed The results of this study indicate that NPC can have nine variations of behavior that can change according to these conditions.